Pemanfaatan Teknologi Informasi sebagai Media Pembelajaran Daring Pada Masa Pandemi Covid-19 - ahmad widi nugroho wakiran (Elementa: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
Abstract This study aims to determine the use of information technology as an online learning medium during the Covid-19 pandemic. By using various platforms such as: Google Classroom, YouTube, Googlemeet, zoom meeting, WhatsApp. The research was conducted by means of a qualitative approach. This study uses a qualitative approach by collecting data through the literature review method. Then the results show that information and communication technology has many roles and benefits, especially in the world of education such as during online learning as it is today due to the Covid-19 virus pandemic. By conducting a literature review of journals obtained from Google Scholar regarding the use of information and communication technology as online learning media during the COVID-19 pandemic, it can be concluded that information and communication technology has been used in online learning as a learning medium such as: Google Classroom, YouTube, Googlemeet, zoom meeting, WhatsApp.